A Review: Improving Scientific Attitudes through Physics Learning Media with PjBL Model - Aris Doyan; Susilawati Susilawati; Ahmad Harjono; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti; Hamidi Hamidi (Jurnal Penelitian Pendidikan IPA, 2025)
Physics learning media developed using the Project-Based Learning (PjBL) model plays a crucial role in shaping students' scientific attitudes. This research aims to identify and analyze research trends of physics learning media based on PjBL model to improve scientific attitude. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research trend that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. Where the research trend is with an increase in the number of publications every year, namely from 2015 to 2023. However, in 2024 the research trend on the physics learning media based on PjBL model to improve scientific attitude has decreased. There are many documents in the form of articles, proceedings, book chapters, edited, preprint and monograph books that discuss research about the trend. Key words that are often used in research of scientific attitude are critical thinking, scientific literacy, scientific approach, creativity, etc